2019
DOI: 10.1111/cei.13358
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported changes in the expanded disability status scale score in patients with multiple sclerosis after autologous stem cell transplants: real-world data from a single center

Abstract: In order to reset the immune system to baseline function, autologous hematopoietic stem cell transplantation (HSCT) has been performed in patients with multiple sclerosis (MS). After June 2015, 617 new consecutive patients with MS were autografted in our center with non-frozen peripheral blood stem cells. The autografts were performed on an outpatient basis, after conditioning with cyclophosphamide and rituximab. The aim of the study was the assessment of both safety and efficacy of the method. The study's pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Although this study was limited due to the lack of a comprehensive follow-up assessment, i.e., the EDSS score evaluation at the given time points was achieved in 72% of all patients (240 patients at 1 year, 136 at 2 years, and 19 at 3 years). These results could demonstrate a consistent effect across all groups and period of study ( 8 ).…”
Section: Reports On Response and Clinical Evaluationsupporting
confidence: 57%
See 2 more Smart Citations
“…Although this study was limited due to the lack of a comprehensive follow-up assessment, i.e., the EDSS score evaluation at the given time points was achieved in 72% of all patients (240 patients at 1 year, 136 at 2 years, and 19 at 3 years). These results could demonstrate a consistent effect across all groups and period of study ( 8 ).…”
Section: Reports On Response and Clinical Evaluationsupporting
confidence: 57%
“…Having proved that the Mexican HSCT method was both feasible ( 10 ) and safe ( 11 ), we have recently analyzed data of its efficacy in a group of 617 MS patients ( 8 ), this being the largest published single-center experience of HSCT in persons with MS. In this communication, a significant reduction in the EDSS score was achieved in all the three phenotypes of MS (from a median of 5.1 to 4.5 points) 12 months after the transplant, whereas the response rate (defined as a decrease of at least 0.5 of EDSS score regardless of baseline EDSS, or unchanged EDSS) was 83, 78, and 73% after 12 months in the relapsing-remitting, primary-progressive and secondary-progressive forms of MS, respectively.…”
Section: Reports On Response and Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides the experimental background that could be used for establishing a similar procedure in patients—moving a part of the Cy from conditioning into post HSCT treatment. The study of the splitting of the Cy dose into premobilization and conditioning shows very promising results (Ruiz-Argüelles et al 2019 , 2017 ). The approach presented in our study might help to maintain the dose density of chemotherapy and possibly improve the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 44 phase I, I/II, and II studies, as well as registered clinical trials and post hoc analyses on cell therapy for MS, were found, and a summary of the results is shown in Table 1 (for further details, see Supplementary Table S1 ) [ 9 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. The number of included patients in these studies varied between five and 617, with most investigating chronic–progressive forms of MS (five trials included relapsing–remitting MS patients only).…”
Section: Resultsmentioning
confidence: 99%